(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, the morphological changes in the lymphoid structures of the small intestinal wall of a white outbred rat after traumatic brain injury were determined as material and materials taken from the intestine were morphologically examined. Changes in the mucous membrane and intestinal barrier TBI leads to dysfunction of the "brain-gut" axis, which contributes to: atrophy of intestinal villi decrease in their height and thickening of the crypts. This reduces the absorption capacity of the intestine. Due to destruction by enterocytes, it leads to increased intestinal permeability, which contributes to dystrophic changes - vacuolization of the cytoplasm, pycnosis of nuclei, damage to microvilli. Edema of the mucous membrane, stagnation of blood in the capillaries, impaired microcirculation and the formation of microthrombi in small vessels due to endothelial dysfunction.